Osteonecrosis of the Femoral Head: Lipotoxicity Exacerbation in MSC and Modifications of the Bone Marrow Fluid - Gillet, Celine; Dalla Valle, Antoine; Gaspard, Nathalie; Spruyt, Delphine; Vertongen, Pascale; Lechanteur, Jessica; Rigutto, Sabrina; Dragan, Elena-Raluca; Heuschling, Audrey; Gangji, Valerie; Rasschaert, Joanne (Endocrinology (Philadelphia), 2017)
Osteonecrosis of the femoral head (ON) is a multifactorial bone disease that can evolve to a progressive destruction of the hip joint. Different pathogenic processes have been proposed, among them, an increase of bone marrow (BM) fat resulting from adipocyte accumulation. Marrow adipocytes are active BM residents that influence the microenvironment by releasing cytokines, adipokines, and free fatty acids (FA). We explored the impact of palmitate (Palm) and oleate on function and survival of BM-derived mesenchymal stromal cells (MSC) of osteonecrotic patients (ONMSC) and healthy volunteers. Moreover, we analyzed the FA profile of the serum and the BM supernatant fluid (BMSF). We demonstrated that exposure to the saturated FA Palm favored MSC differentiation through the adipogenic lineage at the expense of the osteoblastic phenotype. Moreover, adipogenesis was intensified in ONMSC. The susceptibility to Palm toxicity was aggravated in ONMSC concomitantly with a greater activation of the proapoptotic extracellular signal-regulated kinase pathway. Moreover, cellular mechanisms implicated in the protection against lipotoxicity, such as stearoyl-coenzyme A desaturase 1 and carnitine palmitoyl transferase 1 expression, were dysregulated in ONMSC. Palm-induced interleukin (IL)-6 and IL-8 secretion was also exacerbated in ONMSC. Our results established that, in the serum, the FA profiles were comparable in ON and healthy subjects. However, both the concentrations and the FA composition were modified in the BMSF of ON patients, highlighting a drastic change of the BM microenvironment in ON patients. Altogether, our work suggests that marrow adipocyte enlargement could affect the process of bone remodeling and, therefore, play a role in the pathogenesis of ON.